Sintilimab and Chidamide for Refractory Transformed Diffuse Large B Cell Lymphoma: A Case Report and A Literature Review - Chen, Chao; Zhang, Wei; Zhou, Daobin; Zhang, Yan (Frontiers in Oncology, 2021)
Relapsed/refractory (R/R) transformed diffused large B cell lymphoma (tDLBCL) has a poor prognosis, studies about new therapies for tDLBCL are scarce. PD-1 antibody and histone deacetylase inhibitor both have anti-lymphoma effects but the combination of these two therapies hasn’t been explored in DLBCL. Here, we present a successful combination therapy of sintilimab and chidamide for R/R tDLBCL. The patient was a 71-year-old man with pulmonary mucosa-associated lymphoid tissue lymphoma. He didn’t receive any treatment until transformed DLBCL was confirmed 2 years later. The tDLBCL was primary refractory to R2-CHOP, R2-MTX, and Gemox regimens. However, he achieved sustained complete remission after the combination therapy of sintilimab and chidamide. According to our knowledge, this is the first report of sintilimab combined with chidamide for treatment of R/R tDLBCL, which opens up new therapeutic possibilities of this new combination therapy in future prospective clinical trials.